Pribumi Primary Education at Colonial Era (1900-1920) - Cyntia Ayu Lestari; Sumardi Sumardi; Nurul Umamah; Marjono Marjono; Riza Afita Surya (JURNAL HISTORICA, 2023)
This research discusses specfic primary education for pribumi children during the Dutch colonial period 1900-1920. To find out the forming and condition of indigenous primary schools that were established and operating, the researchers conducted this research with the following objectives: (1) to analyze the establishment of indigenous primary education during the Dutch colonial period 1900-1920 and (2) to analyze the implementation of indigenous primary education during the Dutch colonial administration in 1900-1920. The research method used consists of 5 steps namely: topic selection, heuristics, verification, interpretation, historiography. The results show that the establishment of indigenous primary education in Indonesia during the Dutch colonial period was based on political-economic interests carried out by the government. The Dutch colonial government needed employees who could help on the plantations as clerks. Meanwhile, the problem of illiteracy among the indigenous people is still very high. Because of this, schools were opened for the Bumiputera community to educate prospective government employees who could read and write. The limitations of these goals resulted in minimal development in this Bumiputera school curriculum. Keywords: primary education, pribumi, colonial dutch period.